Chemical composition and ruminal degradation of the mesquite pod (Prosopis spp.) at different maturity stages - Montañez-Valdez, Oziel Dante; Reyes-Gutiérrez, José Andrés; Ley-de Coss, Alejandro; Vicente-Pérez, Ricardo; Gómez-Vázquez, Armando; Guerra -Medina, Cándido Enrique (Ecosistemas y Recursos Agropecuarios, 2021)
The aim of this study was to evaluate the chemical composition and in situ digestibility (DIS) of the dry matter (DM) and organic matter (OM) matter of the pods from Mesquite (Prosopis spp.) at different maturity stage in the location of Usmajac, Sayula County, Jalisco, Mexico. The evaluated treatments were: T1) Tender pods; strong green color with seeds still in formation; T2) Mature pods; intense purple with green lines and soft texture; and T3) Dry sheath; Pale purple color and with fully formed seeds, thick pods with a hard texture. The chemical composition of the pods was evaluated. The DIS was calculated using two Holstein steers with permanent ruminal cannula, quadruplicate samples of each experimental treatments were incubated for 16, 24, 36, 48, 72, 96 h. Tender pod, had the highest content of crude protein, T2 and T3 had the highest content of non-fibrous carbohydrates. Differences were found between treatments in the DIS of the DM (P ≤ 0.05), the mature pods showed the highest values. There was a significative difference between treatments in the DIS of the OM (P 0.05). According to the chemical composition and the in situ digestibility, it is concluded that the mesquite pods can be considered as an alternative feed resource for ruminants during the dry season.